1990
DOI: 10.1097/00001888-199012000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Score reporting on NBME examinations

Abstract: Because the National Board of Medical Examiners (NBME) will introduce new comprehensive Part I and Part II examinations in 1991, a review has been made of score reporting methods to be used in the new examinations. The review was conducted also because of concern expressed by some that NBME examination scores are misused in medical schools and in resident selection. In this paper, selected aspects of score reporting are defined, the uses of score reports outlined, and the potential for misuse described. It sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Numerical scores have been reported on all NBME examinations since 1916, 8 and prior to the CEUP, the NBME upheld this practice following reviews of its scorereporting policy in 1989 9 and 1997. 8 Reporting of numerical scores has prompted an ongoing debate because Emergency medicine 25 (3) Internal medicine/pediatrics…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerical scores have been reported on all NBME examinations since 1916, 8 and prior to the CEUP, the NBME upheld this practice following reviews of its scorereporting policy in 1989 9 and 1997. 8 Reporting of numerical scores has prompted an ongoing debate because Emergency medicine 25 (3) Internal medicine/pediatrics…”
Section: Discussionmentioning
confidence: 99%
“…1,5,8 Medical student preference for pass/fail scoring has varied over time. In the review conducted by the NBME in 1989, 9 fewer than half of all respondents favored pass/fail scoring for either Step 1 or 2. In its more recent review conducted in 1997, 8 61% were in favor of pass/fail scoring, and although the CEUP did not provide specific figures, it reported that surveys of medical student leaders revealed a strong preference for pass/fail scoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted previously, the USMLE is a licensing examination and is not designed to predict future performance on other examinations nor is it designed to predict resident performance or, ultimately, the quality of the practice of medicine. Test results can be biased by medical school characteristics and curricula that are patterned on a USMLE format, resulting in substantial advantages to those students taking the examination 28,29 . Fine and Hayward 30 reported that the performance of internal medicine residents, as measured by faculty evaluations, was most strongly correlated with honors during the medical school internal medicine clerkship, as opposed to NBME scores.…”
Section: Discussionmentioning
confidence: 99%